About the optimal displacement power factor of electric power supply systems - Дорошенко, Олександр Іванович (Technology audit and production reserves, 2015)
Based on the physics of electric power transmission in electric power systems, it is proposed during the calculations of modes not use the peak value of reactive power, which it is usually operated in this case and its current value. This is possible because mathematically and practically reactive electric power as part of the internal electric power of electric power system varies sinusoidally and increases active losses and reduces the carrying capacity of electric power networks of specific electric power consumers and electric power supply networks of organizations. It is proposed the algorithms of damage determination from reactive load of electric power transmission based on consideration of its displacement power factor that must meet the current value of its reactive power. It is argued that the practice of billing calculation for reactive load of electric power consumers that exists in our time because at the state level, there are regulations that require such payment that neither theoretically nor practically impossible. It is obvious that such practice contradicts the moral and legal norms and must be stopped.